Nutrition Literacy in School-age and Teenage Groups: Systematic Review - Senkham, Kunlanant; Chotivichien, Saipin; Tutchananusorn, Sasiporn (Journal of Nutrition Association of Thailand (Online), 2025)
This study aimed to synthesize empirical evidence on the levels, approaches, outcomes, and influencing factors of nutrition literacy (NL) among school-age children and adolescents through a systematic review conducted in accordance with the PRISMA 2020 guidelines, and the methodological quality assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Literature searches were performed in PubMed, ScienceDirect, Springer Nature Link, and the Thai Journal Citation Index (TCI; Groups 1–2), covering publications from 2020 to 2024. A total of 306 records were identified, of which 31 studies met inclusion criteria and quality thresholds and were included in the narrative synthesis. The majority of the included studies were conducted in Asian countries and predominantly employed cross-sectional designs, with limited intervention and program development research. Overall, nutrition literacy were low to moderate, with knowledge-related dimensions outperforming skill-based ones. In particular, functional and critical nutrition literacy skills—such as reading food label, appraising nutrition information credibility, and applying knowledge to daily food choices—were identified as key gaps. Higher levels of nutrition literacy were positively associated with diet quality, dietary diversity, healthy dietary patterns, and selected health-related behaviors, including physical activity and adequate sleep, whereas associations with body mass index were inconsistent. Facilitating factors commonly identified across studies included parental education, particularly maternal education, supportive home and school food environments, experiential and hands-on learning approaches, and social support. In contrast, major barriers included household food insecurity, socioeconomic inequalities, limited access to clear and comprehensible nutrition information, the pervasive influence of unhealthy food marketing and media exposure, and school curricula that emphasized theoretical knowledge over practical skill development. The findings suggest that effective promotion of nutrition literacy among children and adolescents should move beyond knowledge-based education toward skill-oriented and context-sensitive strategies that integrate families, schools, and supportive food environments to foster healthy eating behaviors, reduce long-term risks of non-communicable diseases, and promote sustainable long-term well-being.